O monaquismo segundo Doroteu de Gaza e práticas filosóficas estoicas: aproximações - Fagundes, Alvimar Eustáquio Barcelos (2011)
Dorotheus of Gaza is a sixth century Christian monk whose understanding of the monachism is firmly grounded on the tradition passed on to him by the fathers of the desert. His reflections upon some of the ascetic practices such as the anachoret, renouncements, the constant examination of the heart, the meditation upon evil and death, besides spiritual guidance, can all be closely linked to some philosophical stoic exercises. Some stoic notions are set very far from the fundamental Christian dogmas and, yet, we can see some sort of continuity among Portico philosophers and the Christian monks